THE 'MARIA SCREENING INSTRUMENT’ FOR POST-OPEN PROSTATECTOMY BLEEDING RISK: A QUALITATIVE STUDY - Gorety, Maria; Winarto, Eko; Utama, Julvainda Eka Priya (Fakultas Ilmu Kesehatan, Universitas Ibn Khaldun, Bogor, 2024)
Construction of the Maria Screening Instrument Risk of Bleeding Post Open Prostatectomy” is a guide used to assess the risk of bleeding after open prostatectomy. Patients require 85% blood transfusion when resection exceeds 80% of the prostate. The surgical complications that are feared during open prostatectomy surgery are bleeding and obstruction of urine flow. This study aims to identify, analyze and develop a screening instrument for the risk of bleeding after open sprostatectomy. The author conducted a qualitative exploration with 6 participants from different professions in a Focus Group Discussion (FGD) to get a picture of the need for instruments to become a necessity at Boven Digoel Regional Hospital, followed by expert consultation and revisions according to suggestions. The MARIA instrument is the choice for observing post-open prostatectomy patients, namely: Minimizing Blood Loss, Assuring Safe Treatment. Reducing Complications, Individualizing Care, Accelerating Recovery. Conclusion. Maria's screening instrument as a guide is needed to assess the risk of post-open prostatectomy bleeding. Assessment of post-prostatectomy patients should use assessment instruments that can be developed according to hospital needs.